FRI0204 Radiographic progression of spondyloartritis patients after 13 years of follow up: data from the regisponser database. (12th June 2018) - Pérez Sánchez, L.; Font, P.; López, C.; Bautista, L.; Ladehesa, L.; Gómez, I.; Escudero, A.; Collantes, E.; Castro, M.C.
Abstract : Objectives: To describe the radiographic evolution after 13 years of follow-up in a monographic consultation of patients with Axial Spondyloarthritis ( EspAax) included in REGISPONSER at the Reina Sofía University Hospital in Córdoba. Methods: Seventy eight SpA patients from the REGISPONSER registry were analysed in an observational study, which were evaluated for the first time in the year 2004–2005. The last x-rays analysis of the cervical and lumbar spine, pelvis and hips were recorded. Two independent observers evaluated the radiographs and calculated the BASRI index. The interobserver concordance was studied using Cohen's Kappa statistic. Finally, radiographic progression was assessed using the McNemar test. Results: Sixty one SpA patients were radiographicaly evaluated at baseline and after 11 (1.7) years of follow-up. A complete radiographic study was recorded in 38 of them. The baseline characteristics, including BASRI values, as well as the treatment received are listed in table 1. The strength of the interobserver concordance in the radiographic analysis was considerable in hips (k=0.77, p<0.001) and almost perfect at the levels of the cervical spine (k=0.88, p<0.001), lumbar spine (k=0.87, p<0.001) and sacroiliac joints (k=0.84, p<0.001). The BASRIs and BASRIt scores were 7.5 (2.9) and 8.8 (4.1) respectively. Moreover, during the follow-up, the BASRIt was increased in 1.23 (p=0.014). Individual analysis of the different components of BASRI, showed that 42.1% of SpA patients got worse regarding the score corresponding to the cervical spine (p<0.001), 28.9% to the lumbar spine (p=0.057), 15.8% to the hip (p=0.754) and no worsening was found in sacroiliac (p=0.500). Conclusions: This study provides information related to the structural progression of patients followed in a monographic consultation of SpA after 13 years of follow-up. Radiographic evolution was significantly noticed in relation to the total score of the BASRI. However, analysing the individual scores it seems that the cervical spine was the segment where there was greater radiographic progression. We did not find worsening of BASRI in sacroiliac due to the fact that the most of patients already had an advanced degree of sacroileitis in the first visit of the registry. Disclosure of Interest: None declared